Computing the Jacobian in Gaussian Spatial Autoregressive Models: An Illustrated Comparison of Available Methods. Issue 2 (10th April 2013) - Bivand, Roger; Hauke, Jan; Kossowski, Tomasz
Abstract : When estimating spatial regression models by maximum likelihood using spatial weights matrices to represent spatial processes, computing the Jacobian, ln(|I − λW|), remains a central problem. In principle, and for smaller data sets, the use of the eigenvalues of the spatial weights matrix provides a very rapid resolution. Analytical eigenvalues are available for large regular grids. For larger problems not on regular grids, including those induced in spatial panel and dyadic (network) problems, solving the eigenproblem may not be feasible, and a number of alternatives have been proposed. This article surveys selected alternatives, and comments on their relative usefulness, covering sparse Cholesky and sparse LU factorizations, and approximations such as Monte Carlo, Chebyshev, and using lower‐order moments with interpolation. The results are presented in terms of component‐wise differences between sets of Jacobians for selected data sets. In conclusion, recommendations are made for a number of analytical settings. Al estimar modelos de regresión espacial con el método del máxima verosimilitud (máximum likelihood) y usando matrices de pesos espaciales para representar procesos espaciales, cálculo del término jacobiano ( jabobian) —ln(|I −λW |)‐ sigue siendo un problema central. En principio, y para bases de datos más pequeñas, el uso de los valores propios ( eigenvalues) de la matriz de pesos espaciales proporciona una solución muy rápida. Los eigenvalues analíticos para retículas o grillas grandes y regulares son ya conocidos. Para problemas más grandes, que no se presentan en mallas regulares ‐incluyendo aquellos que se inducen en problemas de paneles espaciales y en problemas de (redes) diádicas‐, es posible que resolver el eigenproblem no sea posible. Este artículo estudia una selección de alternativas y comenta acerca de su relativa utilidad. Se cubren las facorizaciones de tipo Cholesky disperso ( sparse Cholesky ) y de tipo LU dispersas ( sparse LU ), las aproximaciones Monte Carlo, y Chebyshev, así mismo se utiliza momentos de bajo‐orden ( lower‐order ) con interpolación. Los resultados se presentan en términos de diferencias de componentes entre sets de términos jacobianos para bases de datos seleccionadas. En conclusión, se hacen recomendaciones para una serie de contextos analíticos. 当采用表征空间过程的空间权重矩阵对空间回归模型进行最大似然估计时，雅可比矩阵ln(|I−λW|)的计算仍是核心问题。对于小数据集，原则上可利用空间权重矩阵的特征值提供一种快速的解决方案，对于大型规则格网数据特征值分析同样有效。但对于不规则格网大型问题，包括从空间面板和二元（网络）问题中引伸的问题，利用特征值的解决方案可能不适用，对此学术界提出了多种可选替代方案。本文选取已有的几种替代方案并评论各自的相对有效性，其中包括稀疏Cholesky分解和稀疏LU分解法，Monte Carlo和 Chebyshev近似模拟法以及低阶矩插值法。结果以所选数据集雅可比矩阵间特定组份的差异方式显示。最后，推荐了一些分析设定。